PROSES MORFOLOGIS DERIVASI VERBA BAHASA LAMAHOLOT DIALEK TENAWAHANG - Witak, Paulus; Pamantung, Rina; Imbang, Djeinnie (Universitas Sam Ratulangi, 2020)
The morphological process or word formation in the Indonesian language occurred includes several ways and one of them is by affixation in the form of base into a new form. Through the process of affixation there was a change in the form and meaning of the word is called derivation which is the process of affixation which changes the word class . It is the case also in the Lamaholot language dialect of Tenawahang(BLDT). The research is using the methods of qualitative descriptive. The purpose of this research was to determine : 1).What affixes that included in verb derivation of BLDT. 2). How is the process of verb derivation in BLDT . Verb derivation is a change in word class from verb to another word class. The verb derivation that occurs in BLDT includes the noun deverbal and the adjective deverbal . The verb derivation that change the word class of base verb into noun is called noun deverbal , and change the word class of base verb into adjective is called adjective deverbal . Results of the study showed that process of verb derivation which occur in BLDT is the process of affixation that includes prefix: be-; infix:-en-; suffixes: -eng,-ung; confix:ke-…-ng. The process of verb derivation that occur can be formed and the meaning are generated as a result of verb derivation in BLDT certainly changed in accordance with the base of word. Key words: affixation, verb derivation, Lamaholot language dialect Tenawahang